2004
DOI: 10.1074/jbc.m404203200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of the Mitotic Kinesin Eg5

Abstract: Eg5 is a slow, plus-end-directed microtubule-based motor of the BimC kinesin family that is essential for bipolar spindle formation during eukaryotic cell division. We have analyzed two human Eg5/KSP motors, Eg5-367 and Eg5-437, and both are monomeric based on results from sedimentation velocity and sedimentation equilibrium centrifugation as well as analytical gel filtration. The steady-state parameters were: for Eg5-367: Eukaryotic cell division requires proper assembly and maintenance of the bipolar spindle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
122
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(144 citation statements)
references
References 86 publications
(74 reference statements)
20
122
2
Order By: Relevance
“…The apoEg5 protein preparations were tested for activity by measuring the steadystate ATPase kinetics as a function of microtubule concentration at saturating MgATP, and as a function of MgATP concentration at saturating microtubule concentration (Table 1). These experiments demonstrated that, under the same experimental conditions as previous studies (13), apoEg5 retained 95-99% of its microtubule-activated ATPase activity. In addition, pulsechase, acid-quench, and P i release experiments were performed using the purified apoEg5 in the presence of microtubules, and we observed full burst amplitude from each transient, demonstrating that the entire population of apoEg5 sites was fully active.…”
Section: Apoeg5 Was Active and Nucleotide-freesupporting
confidence: 80%
See 3 more Smart Citations
“…The apoEg5 protein preparations were tested for activity by measuring the steadystate ATPase kinetics as a function of microtubule concentration at saturating MgATP, and as a function of MgATP concentration at saturating microtubule concentration (Table 1). These experiments demonstrated that, under the same experimental conditions as previous studies (13), apoEg5 retained 95-99% of its microtubule-activated ATPase activity. In addition, pulsechase, acid-quench, and P i release experiments were performed using the purified apoEg5 in the presence of microtubules, and we observed full burst amplitude from each transient, demonstrating that the entire population of apoEg5 sites was fully active.…”
Section: Apoeg5 Was Active and Nucleotide-freesupporting
confidence: 80%
“…Figure 2 shows that the maximum observed rate of MgATP turnover by apoEg5 was 0.02 s −1 , similar to former Eg5 preparations (13), with a very tight K m,ATP at 0.17 μM. The K m,ATP was greater than 40-fold tighter in the absence of microtubules compared to microtubule-activated steady-state ATPase: 0.17 μM (apoEg5) versus 6.95 μM (Mt·Eg5) ( Table 1).…”
Section: Steady-state Atpase Reveals Tight Atp Binding Yet Inefficiesupporting
confidence: 72%
See 2 more Smart Citations
“…Labeling stoichiometries of 1.7-1.9 were achieved for both constructs (data not shown). The MT-activated k cat for TMR-labeled V256C,V365C was 5.1 Ϯ 1.6 s Ϫ1 , whereas that for TMR-labeled A2C,V256C was 4.5 Ϯ 0.9 s Ϫ1 , both reasonably close to the corresponding value for wild type (33). Additionally, labeling with the FRET donor/acceptor pair AEDANS-DDPM was accomplished by incubating the motor domain construct with 0.2 mol eq of 1,5-IAEDANS for 24 h, followed by incubation with a 10-fold molar excess of DDPM.…”
Section: Methodssupporting
confidence: 48%